A Water Stable, Near‐Zero‐Strain O3‐Layered Titanium‐Based Anode for Long Cycle Sodium‐Ion Battery. (17th December 2019) - Cao, Yang; Zhang, Qing; Wei, Yaqing; Guo, Yanpeng; Zhang, Zewen; Huang, William; Yang, Kaiwei; Chen, Weihua; Zhai, Tianyou; Li, Huiqiao; Cui, Yi
Abstract: Layered transition metal (TM) oxides of the stoichiometry Na x MO2 (M = TM) have shown great promise in sodium‐ion batteries (SIBs); however, they are extremely sensitive to moisture. To date, most reported titanium‐based layered anodes exhibit a P2‐type structure. In contrast, O3‐type compounds are rarely investigated and their synthesis is challenging due to their higher percentage of unstable Ti 3+ than the P2 type. Here, a pure phase and highly crystalline O3‐type Na0.73 Li0.36 Ti0.73 O2 with high performance is successfully proposed in SIBs. This material delivers a reversible capacity of 108 mAh g −1 with a stable and safe potential of 0.75 V versus Na/Na + . In situ X‐ray diffraction reveals that this material does not undergo any phase transitions and exhibits a near‐zero volume change upon Na + insertion/de‐insertion, which ensures exceptional long cycle life over 6000 cycles. Importantly, it is found that this O3‐Na0.73 Li0.36 Ti0.73 O2 shows superior moisture stability, even when immersed into water, which are both elusive for conventional layered TM oxides in SIBs. It is believed that the small interlayer distance and high occupation of interlayer vacancy promise such unprecedented water stability. Abstract : O3‐Na0.73 Li0.36 Ti0.73 O2 is first achieved as an anode for sodium‐ion batteries (SIBs). It delivers a reversible capacity of 108 mAh g −1 with near‐zero strain and no phase transitions, ensuring excellent cycle stability over 6000 cycles. More surprisingly, in contrast to the 32% capacity drop of the P2‐type material, this O3‐type material shows excellent water stability among layered transition metal oxides in SIBs.